Answer: x=3
Step-by-step explanation:
To solve this problem you must apply the proccedure shown below:
- Multiply both sides of the equation by 3:
![3(2x-3)=3(\frac{x^2}{3})\\6x-9=x^{2}](https://tex.z-dn.net/?f=3%282x-3%29%3D3%28%5Cfrac%7Bx%5E2%7D%7B3%7D%29%5C%5C6x-9%3Dx%5E%7B2%7D)
- Now you must make the equation equal to zero as following:
![6x-9=x^{2}\\x^{2}-6x+9=0](https://tex.z-dn.net/?f=6x-9%3Dx%5E%7B2%7D%5C%5Cx%5E%7B2%7D-6x%2B9%3D0)
- Factor it, as you can see below. Therefore, you obtain the following result:
![(x-3)(x-3)=0\\(x-3)^2=0\\x=3](https://tex.z-dn.net/?f=%28x-3%29%28x-3%29%3D0%5C%5C%28x-3%29%5E2%3D0%5C%5Cx%3D3)
y=(c+b)/ab. Hope this helped, could I possibly get brainliest?
Answer:
3x+4x
Step-by-step explanation:
you should get your answer
Answer:
x is-4,and ans for y is 1
Step-by-step explanation:
Here you go, you have to use Pythagorean’s theorem